Improving public sector efficiency for more inclusive growth in Latvia - Klein, Caroline (OECD Publishing, 2015)
This working paper explores avenues to improve public sector efficiency in Latvia, a catching-up and ageing economy where spending needs are large. Ensuring that spending allocated to core services (e.g. education, healthcare) is adequate to achieve convergence of policy outcomes to OECD upper standards is challenging. Efficiency gains in the tax system could bring additional revenues. The tax base should be expanded by reducing informality, strengthening tax administration and increasing property and environmentally related taxes, which are low by international standards. To reduce unemployment and income inequality, the tax-benefit system should also be revised as it is now relatively regressive and the tax wedge on low-income earners is high. Enhancing analytical, monitoring and assessment capacities should help to rein in wasteful expenditure and improve the prioritisation of spending. The reform of human resource management, public procurement, and state-local relations is also needed to deliver higher-quality and more cost-efficient public services
Keywords: Economics; Latvia